Influence of lateral pressure to the implant bed on osseointegration: an experimental study in dogs - Pantani, Fabio [UNESP]; Botticelli, Daniele; Garcia, Idelmo Rangel [UNESP]; Salata, Luiz Antonio; Borges, Germana Jayme; Lang, Niklaus P. (Wiley-Blackwell Publishing, Inc, 2010)
AimTo study osseointegration and bone-level changes at implants installed using either a standard or a reduced diameter bur for implant bed preparation.Material and methodsIn six Labrador dogs, the first and second premolars were extracted bilaterally. Subsequently, mesial roots of the first molars were endodontically treated and distal roots, including the corresponding part of the crown, were extracted. After 3 months of healing, flaps were elevated and recipient sites were prepared in all experimental sites. The control site was prepared using a standard procedure, while the test site was prepared using a drill with a 0.2 mm reduced diameter than the standard one used in the contra-lateral side. After 4 months of healing, the animals were euthanized and biopsies were obtained for histological processing and evaluation.ResultsWith the exception of one implant that was lost, all implants were integrated in mineralized bone. The alveolar crest underwent resorption at control as well as at test sites (buccal aspect similar to 1 mm). The most coronal contact of bone-to-implant was located between 1.2 and 1.6 mm at the test and between 1.3 and 1.7 mm at the control sites. Bone-to-implant contact percentage was between 49% and 67%. No statistically significant differences were found for any of the outcome variables.ConclusionsAfter 4 months of healing, lateral pressure to the implant bed as reflected by higher insertion torques (36 vs. 15 N cm in the premolar and 19 vs. 7 N cm in the molar regions) did not affect the bone-to-implant contact.To cite this article:Pantani F, Botticelli D, Garcia IR Jr., Salata LA, Borges GJ, Lang NP. Influence of lateral pressure to the implant bed on osseointegration: an experimental study in dogs.Clin. Oral Impl. Res. 21, 2010; 1264-1270.doi: 10.1111/j.1600-0501.2009.01941.x.
Keywords: animal study; bone healing; histology; implant dentistry; osseointegration; torque